KEBERANIAN SEEKOR TIKUS: KARAKTERISASI THE BOY DALAM THE WITCHES KARYA ROALD DAHL - Ni Komang Arie Suwastini; Ni Komang Julia Dewi; Nyoman Pasek Hadi Saputra; I Putu Ngurah Wage Myartawan (Yavana Bhasha : Journal of English Language Education, 2022)
This study aims to analyze the character of The Boy as the main protagonist character in Roald Dahl's The Witches. The researcher collected the data by using the method of close reading and note-taking. As the main protagonist in the novel, The Boy was described as cheerful, curious, brave, and intelligent. He was described to be optimistically move on with his life after his parents’ deaths and after he was turned into a mouse. He was also a curious child, which lead him to investigate the witches' activity at the resort. As a brave and intelligent mouse, The Boy found tricks to tackle the Grand Witch and her army of witches. As a child who was turned into a mouse The Boy’s characterizations enabled him to save other children from being turned into a mouse. These characterizations could inspire children and readers in general to be optimistic in facing life.